2004
DOI: 10.1159/000077914
|View full text |Cite
|
Sign up to set email alerts
|

Uteroplacental Hemodynamics during Early Human Pregnancy: A Longitudinal Study

Abstract: Background: To determine normal physiologic changes in the uteroplacental hemodynamics during early placental development in the first trimester of pregnancy. Methods: Sixteen normal singleton pregnancies were included in this longitudinal study. Transvaginal Doppler ultrasonographic examinations of uterine, arcuate, radial and spiral arteries were performed at the 5th, 7th, 8th and 10th completed gestational weeks. Peak systolic velocity (PSV), time-averaged maximum velocity (TAMXV) and the pulsatility index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 22 publications
(26 reference statements)
3
45
0
Order By: Relevance
“…Impaired function of those vessels can result in further pregnancy complications (i.e., intrauterine growth restriction or pregnancy-induced hypertension). Serial measurements conducted by Makikalio et al (19) demonstrated a gradual decrease in the spiral artery PI at 5-10 weeks of uncomplicated pregnancy (from 0.93 Ϯ 0.3 to 0.67 Ϯ 0.3).…”
Section: Discussionmentioning
confidence: 98%
“…Impaired function of those vessels can result in further pregnancy complications (i.e., intrauterine growth restriction or pregnancy-induced hypertension). Serial measurements conducted by Makikalio et al (19) demonstrated a gradual decrease in the spiral artery PI at 5-10 weeks of uncomplicated pregnancy (from 0.93 Ϯ 0.3 to 0.67 Ϯ 0.3).…”
Section: Discussionmentioning
confidence: 98%
“…This progressive dilation is reflected in sonographic measurements demonstrating that the peak systolic velocity and pulsatility index are higher in the uterine artery compared to the arcuate artery (Fig. 3) [23].…”
Section: Anatomy Of the Uteroplacental Circulationmentioning
confidence: 94%
“…18 The association between vaginal bleeding and preterm delivery has also been noted by others. 19 Both Batzofin et al and Williams et al reported that patients with bleeding had double the risk of preterm delivery compared with patients without bleeding. 17,20 The study of Williams et al was limited to first trimester bleeding.…”
Section: Preterm Birthmentioning
confidence: 99%